The Study of Using Recycled Chemical Floc for Reducing Chemical Doses in Water Treatment Process (Case Study: Ciliwung Water River at Bojong Gede Sub-District) - Aura Ryumandhina Aninditya; Temmy Wikaningrum (Fakultas Teknik, 2022)
Good water quality following to the criteria for clean water, a series of treatments is needed. One of the processes that aim to reduce turbidity value is coagulation-flocculation. To achieve the maximum result, optimum doses of coagulant are needed. This study aimed to explore the potential for the reuse of chemical flocs to reduce the optimum dose and effect on pH and water turbidity values. The method used is laboratory experiment using a jar test with rapid and slow stirring of 180 rpm for 90 seconds and 40 rpm for 10 minutes, respectively with 30 minutes of sedimentation. The characteristics of the flocs used are 76% from PAC with variants volume from 0.5 ml to 3 ml, which impact decreasing the optimum dose by 50% with achievement of turbidity value 0.16 NTU or equivalent to 99.65% reduction efficiency. Using the T-Test Two-Sample Equal Variances between the optimum dose turbidity value and decreasing the dose combined with the recycled floc, the p-value less than 0.05, means that chemically recycled has a significant different on the turbidity value. Meanwhile, the p-value obtained between the pH value before and after the addition of recycled flocs is less than 0.05, hence the water after treatment has less acidic than the conventional method. Water pH is significant different showed as less reduction of pH by having recycled PAC flocs.